2009
DOI: 10.1042/bj20082277
|View full text |Cite
|
Sign up to set email alerts
|

High ambient glucose induces angiotensin-independent AT-1 receptor activation, leading to increases in proliferation and extracellular matrix accumulation in MES-13 mesangial cells

Abstract: Diabetic nephropathy is associated with mesangial ECM (extracellular matrix) accumulation. We have shown that AT-1R [Ang II (angiotensin II) type I receptor] signalling induces ECM proteins via transactivation of PI3K (phosphoinositide 3-kinase) in mesangial cells. In the present study, we examined the mechanisms underlying the effect of high ambient glucose on cell proliferation and ECM expansion in a mesangial context. High glucose induced increases in PI3K activity, proliferation and ECM accumulation in mes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
23
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 49 publications
3
23
0
Order By: Relevance
“…The frequent pathological characteristics of DN are the hypertrophy of glomerulus and kidney tubules, the broadening of mesangial area, the degeneration of vacuoles and the appearing of irregular shape epithelium in partial kidney tubules (Ayo et al ., 1990; Yano et al ., 2009), which may ultimately result in glomerular sclerosis and renal fibrosis. In this study, we observed that hypertrophy of glomerular and renal tubular was alleviated, basement membrane was not thickened, mesangial area was not obviously broadened, vacuoles degeneration was reduced in renal tubular epithelia in SDO, DSS, Pae, and DSS+Pae treatment groups.…”
Section: Discussionmentioning
confidence: 99%
“…The frequent pathological characteristics of DN are the hypertrophy of glomerulus and kidney tubules, the broadening of mesangial area, the degeneration of vacuoles and the appearing of irregular shape epithelium in partial kidney tubules (Ayo et al ., 1990; Yano et al ., 2009), which may ultimately result in glomerular sclerosis and renal fibrosis. In this study, we observed that hypertrophy of glomerular and renal tubular was alleviated, basement membrane was not thickened, mesangial area was not obviously broadened, vacuoles degeneration was reduced in renal tubular epithelia in SDO, DSS, Pae, and DSS+Pae treatment groups.…”
Section: Discussionmentioning
confidence: 99%
“…Whether Met, as a consequence of its modulated metabolism, influences cardiomyocyte survival remains unknown. We have previously reported a pro-survival/proliferation pathway in cardiomyocyte [24], [25] and renal mesangial cells [26], [27] involving G-protein coupled receptor (GPCR)-PKA-Src-receptor tyrosine kinase. The present study provides evidences that AMPK and PKA are activated sequentially following Met treatment.…”
Section: Discussionmentioning
confidence: 99%
“…As in human diabetic nephropathy, the increased expression of several different genes encoding matrix proteins such as collagen and fibronectin contributes to their accumulation in glomerular matrices in diabetic db / db mice. It has been demonstrated that a high glucose concentration stimulates increased synthesis of ECM constituents in cultured mesangial cells [38,39] . In this study, AKF-PD treatment led to a significant reduction in mRNA expression of ␣ 1 (I)-and ␣ 1 (IV)-collagen, and fibronectin in the renal cortex of diabetic db / db mice.…”
Section: Discussionmentioning
confidence: 99%